THE ROLE OF PROFESSIONAL ETHICS IN COMBATING ORGANIZATIONAL POLITICIZATION AT THE UNIVERSITY OF TIKRIT APPLIED RESEARCH - Dr. Firas Hassan Rasheed; Ibrahim Mohammed Saleh; Mezher Abdullah Ahmed (Scholars Digest Publishing, 2024)
The study explores workplace ethics and its role in reducing the politicization of organizations, applying it to a sample of department heads and deans at the University of Tikrit, with a total sample of (60) people, and the opinions of the sample are: Survey There are 22 items in the questionnaire, and the response rate of the respondents is 100%. This study aims to identify the impact of professional ethics on the politicization of organizations among staff at the universities under investigation. The results show that the hypothesis of the correlation and ethical implications of the work ethics dimension in combination with the organizational politicization dimension at the University of Tikrit is valid. The study recommends promoting a work ethics culture at the University of Tikrit. To achieve this goal, reduce the politicization of labor.
Keywords: Job ethics, Organizational politicization